Economic Growth, Financial Development, and Income Inequality - Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2015)
The central objective of our paper is to empirically examine the relationship between financial development and income inequality. Theoretically, there are grounds for both a positive and negative relationship between the two variables. Our main finding is that financial development contributes to reducing inequality up to a point, but as financial development proceeds further, it contributes to greater inequality. We also find that when the ratio of primary schooling to total schooling increases and law and order improves, financial development becomes more effective in reducing inequality.
hdl:11540/5099
Keywords: D63; G01; O11; O40; 330; financial development; growth; income inequality